2020
DOI: 10.1159/000509225
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Impairment in Patients New to Dialysis

Abstract: Background: Impaired mobility is associated with functional dependence, frailty, and mortality in prevalent patients undergoing dialysis. We investigated risk factors for mobility impairment, (poor gait speed) in patients incident to dialysis, and changes in gait speed over time in a 2-year longitudinal study. Methods: One hundred eighty-three patients enrolled within 6 months of dialysis initiation were followed up 6, 12, and 24 months later. Grip strength, health-related quality of life, and comorbidities we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…23 In addition, chronic kidney disease, a common comorbidity in patients with cardiovascular disease, has been reported to be associated with frailty progression. 24 , 25 Although there were few dialysis patients in the present study, a clinical study has shown progression of mobility impairment in this population. 25 We previously demonstrated that, among nonagenarians with AMI who underwent PCI, the proportion of patients with frailty increased during hospitalization, from 43.8% at admission to 60.7% at discharge.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…23 In addition, chronic kidney disease, a common comorbidity in patients with cardiovascular disease, has been reported to be associated with frailty progression. 24 , 25 Although there were few dialysis patients in the present study, a clinical study has shown progression of mobility impairment in this population. 25 We previously demonstrated that, among nonagenarians with AMI who underwent PCI, the proportion of patients with frailty increased during hospitalization, from 43.8% at admission to 60.7% at discharge.…”
Section: Discussionmentioning
confidence: 69%
“… 24 , 25 Although there were few dialysis patients in the present study, a clinical study has shown progression of mobility impairment in this population. 25 We previously demonstrated that, among nonagenarians with AMI who underwent PCI, the proportion of patients with frailty increased during hospitalization, from 43.8% at admission to 60.7% at discharge. 15 We also reported that although not significant in a multivariate analysis, frailty progression was more frequently observed in patients with AMIHF than in those with Killip Class 1 disease.…”
Section: Discussionmentioning
confidence: 69%
“…Patients undergoing dialysis have poor skeletal muscle strength and slowed gait speed that increases the risk of functional dependence, frailty, fractures and falls 1 5 . In 183 patients new to dialysis, we have demonstrated low grip strength (median 27.0 ± 11.5 kg) and slow gait speed (median 0.78 m/s (0.64–0.94)) 2 . In this cohort, multivariate analyses demonstrated low gait speed was associated with several clinical risk factors including overall health utility indices, diabetic nephropathy, and use of a walking aid.…”
Section: Introductionmentioning
confidence: 89%
“…Subjects who were enrolled in the Indiana-University Longitudinal Study of Incident Dialysis (IU-LUCID) were recruited from outpatient dialysis units affiliated with Indiana University Health Nephrology and located in inner-city areas 2 . Briefly, eligible participants were > 18 years old, started dialysis within the past 6 months, and had both plasma metabolites and physical function measurements collected at study initiation.…”
Section: Methodsmentioning
confidence: 99%
“… 22 , 80 , 81 , 96 Handgrip strength might also offer prognostic utility, demonstrating correlation with gait speed and kidney transplant assessment outcomes, as well as sensitivity to change over acute admission. 125 , 156 , 157 However, impairment of lower limb function, rather than upper limb function, is most predictive of outcomes in CKD studies. 22 , 158 …”
Section: Prevalence Of Frailty In Nephrology Populations: An Epidemic...mentioning
confidence: 99%